Aminodi(hetero)arylamines in the thieno[3,2-b]pyridine series: synthesis, effects in human tumor cells growth, cell cycle analysis, apoptosis and evaluation of toxicity using non-tumor cells - Calhelha, Ricardo C. (2012)
Three aminodi(hetero)arylamines were prepared via a palladium-catalyzed C-N Buchwald-Hartwig coupling of methyl 3-aminothieno[3,2-b]pyridine-2-carboxylate with different bromonitrobenzenes, followed by reduction of the nitro groups of the coupling products to the corresponding amino compounds. The aminodi(hetero)arylamines thus obtained were evaluated for their growth inhibitory effect on four human tumor cell lines MCF-7 (breast adenocarcinoma), A375-C5 (melanoma), NCI-H460 (non-small cell lung cancer) and HepG2 (hepatocellular carcinoma). The toxicity to non-tumor cells was also evaluated using a porcine liver primary cell culture (PLP1), established by us. The aminodi(hetero)arylamine with the NH2 group in the ortho position and an OMe group in the para position to the NH of the di(hetero)arylamine, is the most promising compound giving the lowest GI50 values (1.30–1.63 μM) in all the tested human tumor cell lines, presenting no toxicity to PLP1 at those concentrations. The effect of this compound on the cell cycle and induction of apoptosis was analyzed in the NCI-H460 cell line. It was observed that it altered the cell cycle profile causing a decrease in the percentage of cells in the G0/G1 phase and an increase of the apoptosis levels.